Relationship between life aggression and sport aggression among athletes / Cyndra Robert Budull - Robert Budull, Cyndra (2013)
Aggression is one of the characteristic traits that have been related with sport participation that leads to unsportsmanlike behavior among athletes and may contribute into violence. Meanwhile, life aggression is the athlete’s behavior while they are not participating in their competitive sport. The purpose of this study was to identify the relationship between life aggression and sport aggression among athletes. In addition, the differences between life aggression and sport aggression were also explored. A total of 450 male and female SUKIPT athletes aged between 1 8 -2 6 years old from different contact and non-contact sports were selected through purposive sampling participated in this study. Buss Durkee Hostility Inventory Subscales (BDHI) and Bredemeier Athletic Aggression Inventory - Short Form (BAAGI) was used to assess life aggression and sport aggression. Results show that there was no significant difference of life aggression between male and female athletes (p>.05). However, there is a significant difference of life aggression between contact and non-contact sport (p<.05). Results also show that there was a significant difference of sport aggression between male and female athletes (p<.05), contact and non-contact sport (p<.05). Pearson Correlation showed that there was a moderate and positive correlation between life aggression and sport aggression (r=.46) among athletes. Subsequently, Multiple regression analysis showed that type of sport has higher influence on sport aggression compared to gender of participants (ẞ = 72, p< .05). In conclusion, relationship between life aggression and sport aggression among SUKIPT athletes was at a moderate level, however, efforts to identify the aggression factors and promotion of prevention program by sport psychologist on aggression would be beneficial in reducing aggression and increased the sportsmanship values among athletes.